Examine the public health impacts of functional somatic disorders using the DanFunD study. Issue 7 (November 2022) - Jørgensen, Torben; Dantoft, Thomas Meinertz; Weinreich Petersen, Marie; Eriksen Benros, Michael; Poulsen, Chalotte Heinsvig; Falgaard Eplov, Lene; Gormsen, Lise; Frostholm, Lisbeth; Carstensen, Tina Birgitte Wisbech; Holm Eliasen, Marie; Kårhus, Line Lund; Skovbjerg, Sine; et al.
Background: Persistent physical symptoms (e.g. pain, fatigue) are prevalent in the population and some persons may develop a functional somatic disorder (FSD). We still need to explore the limits between general bodily sensations and FSD, and great controversies exist as regard delimitation, occurrence, risk factors, prognosis, and costs of FSD in the general population. This is mainly due to the lack of focused, sufficient powered, population-based epidemiological studies. Material and Methods: The DanFunD study is the largest focused population-based study on FSD and has the potential to answer these crucial questions regarding the FSD disorders. DanFunD has its origin in the Copenhagen area of Denmark and was initiated in 2009 by an interdisciplinary team of researchers including basic scientists, clinical researchers, epidemiologists, and public health researchers. A population-based cohort of nearly 10, 000 people have filled in detailed questionnaires, gone through a thorough health examination, and a biobank is established. The cohort was re-examined after five years. Results: The prevalence of FSD in the Danish population is about 10-15% and is twice as common in women as in men. Persons with FSD report impaired daily activities and low self-perceived health, which qualifies FSD as a major public health problem. The research plan to unravel the risk factors for FSD employs a bio-psycho-social approach according to a detailed plan. Preliminary results are presented, and work is in progress. Likewise, plans for assessing prognosis and health care costs are provided. Conclusion: We invite researchers in the field to collaborate on this unique data material.